AMALIY DARS JARAYONIDA SAMARALI TA’LIM STRATEGIYALARIDAN FOYDALANISH - Amanbayev, M.A. (SCIENCE and SOCIETY, 2025)
In the article, pedagogues make a great contribution to the formation of capable, confident students who are ready to apply their knowledge in real situations in the process of developing and improving skills using effective educational strategies. By carefully considering practical activities, educators not only impart knowledge, but also arouse enthusiasm and interest.
Keywords: reflective practice; effective learning strategies; inclusive environment; interactive technologies; Socratic method; case studies; quizzes; constructive feedback; selection boards; communication skills; active learning techniques; differentiated learning instruction